PELAKSANAAN PEMBERIAN KOMPENSASI PKWT DI PT CLADTEK BI METAL MANUFACTURING - Pancarini, Tri; Irene Svinarky (SCIENTIA JOURNAL, 2022)
The company's obligation to provide compensation to PKWT employees, the legal basis lies in the government regulation number 35 of 2021 Creation Law as implementing regulations.The period of service of PKWT employees to be extended can be compensated under the existing rules should be given after the PKWT period of at least one year ends. The making of this paper aims to find out the implementation of PKWT compensation by the company to its employees as stipulated in the laws and regulations. The research method used by the author is empirical which is carried out by the method of collecting data through interview techniques with interviewees and dissemination of questionnaires. This writing is systematically arranged that is appropriate in relation to the results and discussion of the author's research. The result of this study is that PT Cladtek Bi Metal Manufacturing has tried to implement regulations regarding compensation but has not been fully implemented. Keywords: Compensation; PKWT; Company.